Social protection arrangements for retired mineworkers with physical disabilities in Maseru urban, Lesotho. - Tlhaole, Thuso (My University, 2011)
Social protection is a means of reducing vulnerability on individuals by protecting them against low or declining living standards. This study examines social protection arrangements for mineworkers who retired from the South African mines on account of disabling mine injuries. Over the years, the mining industry has been the source of employment for Lesotho men. Some of the workers have been exposed to occupational injuries that led to their disability and forced retirement. They are thus forced to return to Lesotho where they become dependent on the compensation that they receive from South Africa through Compensation for Occupational Injuries and Diseases Act. The study sought to determine the adequacy of compensation paid to Basotho mineworkers who retired because of disabling mine injuries in Maseru urban. It also investigated existence of complementary social support systems. A qualitative design was utilised in this study as the intention was to obtain in-depth information from the research participants concerning existing social protection arrangements. Semi-structured interview schedule were conducted with both mine workers who retired on account of disabling mine injuries and key informants. The research sample consisted of 47 mine workers who retired on account of disabling mine injuries and 4 key informants that were drawn from the Department of Social Welfare, Ministry of Labour, TEBA (The Employment Bureau of Africa) and National Union of Mine workers. The findings reveal that retired mine workers use most of their compensation income on household expenditures such as food, electricity and fuel. The compensation income ranges from M400 to M5, 000 per month. For the research participants who are at the lower range, the compensation is not adequate because they are below the poverty line. The findings established that the waiting period for compensation was long because only three research participants received their compensation after a waiting period of up to 5 months while the majority waited for more than 5 months. The findings also indicate that the payment of monthly compensation is consistent and paid timely. The results revealed that retired mine workers rely on alternative coping strategies like income generating projects and informal support from relatives and friends. The findings also reveal that the disability status makes it difficult for the beneficiaries to engage in income generating activities thereby exposing them to poverty and income insecurity. The study recommends that government support should be extended to retired mine workers with low compensation income. The study also suggests the introduction of reintegration programmes that would improve the quality of life for retired mineworkers with physical disabilities.
Keywords: Social protection; Social security; Disability; Formal social protection; Informal social protection